Autoimmune encephalitis associated with antibodies against α-enolase sequestrated from degenerating retina in retinitis pigmentosa - Qun Zeng; Jin Ming Lin; Androniki Syrrou; Onur İnam; Sarah Flanagan Wesley; Tongalp H. Tezel (BMC Ophthalmology)
Abstract Background Retinitis pigmentosa is a group of inherited retinal degenerations resulting in photoreceptor cell dysfunction, death, and eventually vision loss. It can be a manifestation of Usher syndrome and has been linked with autoimmune retinopathy and systemic autoimmune diseases. Case presentation We report the case of a 70-year-old woman with retinitis pigmentosa and Usher syndrome who presented with autoimmune encephalitis. Laboratory tests revealed the presence of α-enolase antibodies in the patient’s serum and cerebrospinal fluid, which cross-reacted with the human brain and retina tissues. Conclusions We describe autoimmune encephalitis caused by autoantibodies against sequestrated retinal antigens in retinitis pigmentosa, which can cross-react with brain tissue. This unique case demonstrates the remote effects of retinitis pigmentosa and an autoimmune pathogenetic pathway that triggered autoimmune encephalitis. Several retinal antigens sequestered into systemic circulation with outer retinal degeneration in retinitis pigmentosa can evoke an immune response and thus produce auto-antibodies that can result in autoimmune encephalitis.